Continuous Positive Airway Pressure for Upper Airway Obstruction in Infants with Pierre Robin Sequence. Issue 2 (February 2016) - Amaddeo, Alessandro; Abadie, Veronique; Chalouhi, Christel; Kadlub, Natacha; Frapin, Annick; Lapillonne, Alexandre; Leboulanger, Nicolas; Garabédian, Erea Noel; Picard, Arnaud; Fauroux, Brigitte
Abstract : Summary: The aim of the study was to evaluate noninvasive continuous positive airway pressure as first-line treatment for upper airway obstruction in neonates with Pierre Robin sequence. Forty-four neonates were enrolled and classified in 4 groups: ventilator-dependent patients (severe upper airway obstruction group), patients with clinical upper airway obstruction, an abnormal (moderate upper airway obstruction group) or normal polygraphy (mild upper airway obstruction group), and those with no clinical upper airway obstruction (no upper airway obstruction group). Five neonates in the severe upper airway obstrction group (n = 9) were successfully managed by noninvasive continuous positive airway pressure and 4 required a tracheotomy. The moderate upper airway obstruction group (n = 4) was successfully managed by noninvasive continuous positive airway pressure and the other patients by prone positioning. Continuous positive airway pressure represents an effective treatment of upper airway obstruction in Pierre Robin sequence and may be recommended in selected patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.